Principal's Visionary Leadership in Improving PAI Teachers' Pedagogic Competence in The Era of Society 5.0 - Nurhasanah, Nurhasanah; Erwin, Erwin; Nugraha, Tisna (Arfannur, 2024)
The challenges of the times are increasingly developing so that they become a benchmark for the progress of an educational institution. The principal must provide something new to his educators in schools in the era of increasingly rapid globalization. Visionary leadership is inseparable from the relationship between charismatic leaders in leading in the era of the Industrial Revolution 5.0. The purpose of this study explores the role of visionary leadership of principals in improving the pedagogical abilities of Islamic Religious Education (PAI) instructors in the era of Society 5.0. This era demands the integration of sophisticated technology in education, which requires an increase in the pedagogical competence of teachers. Through library research, this article identifies effective strategies in the context of visionary leadership to improve the quality of PAI learning. The results of the study indicate that visionary principals play a role in directing and inspiring PAI teachers to utilize technology and innovative learning methods.